2-[(2-Methoxyethyl)sulfanyl]-4-(2-methylpropyl)-6-oxo-1,6-dihydropyrimidine-5-carbonitrile - El-Emam, Ali A. (International Union of Crystallography, 2012)
In the title compound, C(12)H(17)N(3)O(2)S, the 4-methyl-2-methylsulfanyl-6-oxo-1,6-dihydropyrimidine-5-carbonitrile part of the molecule is almost planar (r.m.s deviation = 0.062 Å). In the crystal, molecules form centrosymmetric dimers via pairs of N—H⋯O hydrogen bonds.